Peroneal Afferent Nerve Discharges Underlying the Behavioral Response to the Formalin Test. Issue 3 (May 1996) - Abram, Stephen E.; Dean, Caron; O'Connor, Therese C.
Abstract : Background and Objectives: Subcutaneous injection of formalin into the hindpaw of the rat results in a biphasic behavioral response consisting of flinching of the injected paw. It is postulated that the second-phase response is related to sensitization of spinal cord neurons rather than to resumption of peripheral nociceptor activity. Methods: On removal from anesthesia with 3% halothane, 10 rats were given a subcutaneous injection of formalin (5%, 50 μL) into the dorsum of the hindpaw. Behavioral responses to the formalin test were observed for the subsequent hour. In five sodium pentobarbital-anesthetized rats, peroneal afferent nerve activity was recorded for 1 hour following similar subcutaneous injection of formalin. Results: During standard formalin testing in unanesthetized rats, flinching peaked between 1 and 2 minutes following injection (phase 1 response), ceased between 5 and 10 minutes, and recommenced after 15 minutes with a second peak at 45 minutes (phase 2). In sodium pentobarbital-anesthetized rats, peroneal afferent nerve activity increased transiently during the time course of the phase 1 behavioral response but showed no subsequent increase in activity during the ensuing 55 minutes. Conclusions: The results are consistent with the hypothesis that the initial behavioral response to formalin injection is mediated by high peripheral nerve activity, while the second phase is mediated by sensitization of dorsal horn neurons in conjunction with low persistent levels of afferent activity.